EFEKTIVITAS MODEL PEMBELAJARAN BERMAIN BERBASIS NILAI ISLAM TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI: STUDI EKSPERIMEN - Aeni Latifah; Neng Awalia Farida; Erma Rahmawati; Novita Rahmawati; Nurul Dwi Hariyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of a play-based learning model integrated with Islamic values on the social-emotional development of early childhood. The background of this study is based on the suboptimal social-emotional abilities of children, such as empathy, cooperation, and emotional regulation. The research employed a quantitative approach using a quasi-experimental design (nonequivalent control group design). The subjects consisted of 30 children divided into an experimental group and a control group. Data were collected through observation using a social-emotional development instrument. Data analysis was conducted using descriptive and inferential statistics, specifically the t-test. The results indicated a significant improvement in the experimental group compared to the control group, with the t-value greater than the t-table value and a significance level of < 0.05. This finding demonstrates that the play-based learning model integrated with Islamic values is effective in enhancing children's social-emotional development. The study highlights that integrating play activities with Islamic values provides meaningful and enjoyable learning experiences while fostering children's character development. Therefore, this model can serve as an innovative alternative in early childhood education.